A comparative analysis on the effects of perceived enjoyment and perceived risk on hedonic/utilitarian smartphone applications. (2015) - Xiang, Jun Yong; Jing, Lin Bo; Lee, Hyun Soo; Choi, Il Young
Although smartphone applications are widely adopted around the world, empirical studies that examine the user acceptance on different application types are still scarce. This paper empirically compares the effects of perceived enjoyment and perceived risk on hedonic and utilitarian smartphone applications. Our analyses show that perceived enjoyment is a stronger determinant of intention to use a hedonic smartphone application than a utilitarian application. Perceived risk has a significant negative influence on intention to use utilitarian smartphone applications, while it does not have a significant impact on intention to use hedonic applications. Surprisingly, perceived risk has an insignificant effect on perceived usefulness both in utilitarian and hedonic smartphone applications. This study is expected to help service providers in designing smartphone applications and make contributions to the research perspective on mobile computing adoption.